Il periodo indiano di Maria Montessori - Giacomo Cives (Firenze University Press, 2011)
On Maria Montessori (1870-1952), Italian educator of the twentieth century the most successful in the world, there is, also a growing if belated, interest in more recent times also in Italy. So to confine ourselves to two thousand years, studies have appeared on his life and works of great interest, finally showing that its value is recognized beyond resistance of the idealistic and Catholic area survived for a long time. The author investigates these new frontiers of research on the Montessori starting from a new biography dedicated to her which gives attention also to the Indian period.